Self-Expanding Metal Stents Do Not Adversely Affect Long-term Outcomes in Acute Malignant Large-Bowel Obstruction: A Retrospective Analysis. Issue 2 (February 2022) - Browne, Ikennah L.; Mahsin, Md; Drolet, Sebastien; Buie, W. Donald; Heine, John A.; MacLean, Anthony R.
Abstract : BACKGROUND: Self-expanding metal stents as a bridge to surgery in acute malignant large-bowel obstruction has gained popularity. However, long-term oncologic outcomes have not been well established. OBJECTIVE: To investigate long-term oncologic outcomes of patients undergoing curative resection after the placement of a colonic stent compared with emergency surgery for acute malignant large-bowel obstruction. DESIGN: This is a retrospective study. SETTING: All patients presenting at 3 tertiary care centers between April 2002 and December 2012 with a diagnosis of complete malignant large-bowel obstruction were reviewed. Patients with disease distal to the hepatic flexure were selected for analysis. PATIENTS: One hundred twenty-two patients who underwent either emergency surgery or placement of a colonic stent with curative intent were included. INTERVENTIONS: Patients receiving emergency surgery within 24 hours of presenting with obstructive symptoms, including those with failed stents, were included in the emergency surgery group. All patients with clinically successful stent deployment before surgery were included in the stent group. MAIN OUTCOME MEASURES: Overall survival and disease-free survival were calculated using the Kaplan-Meier method. RESULTS: Sixty-four patients underwent emergency surgery, and 58 patients underwent placement of a self-expanding metal stent. Groups were similar in terms of sex, tumor stage and grade, and Charlson and Charlson-Age Comorbidity Index scores. Patients in the surgery group were older than patients in the stent group. There were no differences in the number of lymph nodes harvested, positive nodes, rates of vascular and perineural invasion, or utilization of chemotherapy. Thirty-day mortality after resection was similar between groups (7.41% vs 4.41%; p > 0.05). Patients who underwent colonic stenting as a bridge to surgery had similar 10-year overall survival (40.5% vs 32.7%; p = 0.13) and 10-year disease-free survival (40.2% vs 33.8%; p = 0.26) compared with those who underwent emergency surgery. Similar results were seen on intention-to-treat analysis. LIMITATIONS: This was a small retrospective study. CONCLUSIONS: Stent insertion followed by oncologic resection is associated with similar overall survival and disease-free survival compared with emergency resection. Stent insertion as a bridge to surgery should be considered in patients presenting with malignant colorectal obstruction. See Video Abstract at http://links.lww.com/DCR/B714 Los Stents Metálicos Autoexpandibles No Afectan Negativamente Los Resultados A Largo Plazo En La Obstrucción Maligna Aguda Del Colon: Un Análisis Retrospectivo ANTECEDENTES: Los stents metálicos autoexpandibles como puente a una cirugía en la obstrucción maligna aguda del colon han ganado popularidad. Sin embargo, no se han establecido bien los resultados oncológicos a largo plazo. OBJETIVO: Investigar los resultados oncológicos a largo plazo de los pacientes sometidos a resección curativa después de la colocación de un stent colónico en comparación con la cirugía de urgencia para la obstrucción maligna aguda del colon. DISEÑO: Estudio retrospectivo. ÁMBITO: Entre abril de 2002 y diciembre de 2012, se revisaron todos los pacientes que acudieron a tres centros de tercer nivel con un diagnóstico de obstrucción maligna completa del colon. Se seleccionaron para el análisis los pacientes con enfermedad distal al ángulo hepático. PACIENTES: Se incluyeron 122 pacientes que fueron operados de urgencia o a una colocación de un stent colónico con intención curativa. PROCEDIMIENTOS: Los pacientes que se sometieron a cirugía de urgencia dentro de las 24 horas posteriores a la presentación de síntomas obstructivos; se incluyeron aquellos con stents fallidos en el grupo de cirugía de urgencia. Todos los pacientes con colocación clínicamente exitosa del stent antes de la cirugía se incluyeron en el grupo de stent. PRINCIPALES VARIABLES ANALIZADAS: La sobrevida global y la sobrevida libre de enfermedad se calcularon mediante el método de Kaplan-Meier. RESULTADOS: Sesenta y cuatro pacientes fueron llevados a cirugía urgente y en 58 pacientes se colocó de un stent metálico autoexpandible. Los grupos fueron similares en relación a sexo, estadio y grado del tumor, puntuación de comorbilidad de Charlson y Charlson-Age. Los pacientes del grupo de cirugía eran mayores que los del grupo de stents. No hubo diferencias en el número de ganglios linfáticos recolectados, ganglios positivos, tasas de invasión vascular y perineural o utilización de quimioterapia. La mortalidad a los 30 días después de la resección fue similar entre los grupos (7, 41% frente a 4, 41%; p > 0, 05). Los pacientes que se sometieron a la colocación de un stent colónico como puente a la cirugía tuvieron una sobrevida general a diez años similar (40, 5% vs 32, 7%; p = 0, 13) y una sobrevida libre de enfermedad a diez años (40, 2% vs 33, 8%, respectivamente; p = 0, 26) en comparación a los operados de urgencia. Se observaron resultados similares en el análisis por intención de tratamiento. LIMITACIONES: Estudio retrospectivo reducido. CONCLUSIONES: La utilización de un stent y posteriormente la resección oncológica se asocia a una sobrevida general y una sobrevida libre de enfermedad similar en comparación con la resección de urgencia. La utilización de un stent como puente a la cirugía debe considerarse en pacientes que presentan obstrucción colorrectal maligna. Consulte Video Resumen en http://links.lww.com/DCR/B714 . (Traducción—Dr. Lisbeth Alarcon-Bernes )